The influence of environmental attributes on indicators of wellbeing across greenspace types in virtual landscapes - Scheer, Carson Michael (Kansas State University, 2022)
Psychological benefits of natural environments have been a driving force behind the design of greenspaces for centuries (Eco, 1994; Montford, 2017; Ward-Thompson, 2011). The impact the presence of greenspace has on an occupant’s sense of belonging, safety, and comfort has been broadly investigated (Herzog, 1992; Houlden et al., 2019; Nasar, 1983; Strumse, 1994). However, less attention has been paid to how changes in specific physical attributes of an environment may affect these senses differently across different types of urban greenspaces. The goal of this study is to examine how changes in the temperature of light, vegetation density, and surface texture impact occupants’ sense of belonging, safety, and comfort differently in distinct types of greenspaces. The examined types of public greenspaces include manicured park, unmanicured timber-meadow, streetscape, community garden, and green roof. A series of five-point rating scale surveys was used to collect data from 51 participants in the southeast side of Brush Creek, Kansas City, MO. Participants were selected by convenience sampling at the public library extension, diners, restaurants, coffee shops, and community spaces located within the study area. The data collection was assisted using an Oculus Quest 2 stereoscopic virtual reality (VR) headset, through which participants were able to experience three-dimensionally rendered environments. VR has been shown to be more immersive than traditional photo boards for design research (Wilson & Soranzo, 2015). First, each participant was randomly assigned to one of the aforementioned greenspace types and asked to observe a baseline virtual environment as a control. They then rated their levels of comfort, safety, and belonging on a five-point rating scale. Participants then also indicated whether they see similar scenes near their residences. Secondly, one of the above environmental attributes was then modified, and the participant again rated their levels of comfort, safety, and belonging; this second step was then repeated for each of the three environmental attributes. Demographic data (age, race, gender, and education level) was also collected. This study shows differences in how the participants’ sense of comfort, safety, and belonging may change across different types of environments. For example, vegetation amount was beneficial in timber-meadow environments but not in any others, and surface texture was found to have the most negative impact on streetscapes. The findings of this study offer greater insights into the use of design elements across greenspace typologies to improve neighborhood quality of life through increased sense of belonging, safety, and comfort. The broader outcome of this study relates to its implications in community restoration through urban greening and to further develop the use of VR in design research.
Keywords: Virtual reality; Greenspace typology; Sense of comfort; Sense of safety; Sense of belonging; Environmental attributes